If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(-8n + -4) + 6 = 12 + 6n Reorder the terms: -1(-4 + -8n) + 6 = 12 + 6n (-4 * -1 + -8n * -1) + 6 = 12 + 6n (4 + 8n) + 6 = 12 + 6n Reorder the terms: 4 + 6 + 8n = 12 + 6n Combine like terms: 4 + 6 = 10 10 + 8n = 12 + 6n Solving 10 + 8n = 12 + 6n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-6n' to each side of the equation. 10 + 8n + -6n = 12 + 6n + -6n Combine like terms: 8n + -6n = 2n 10 + 2n = 12 + 6n + -6n Combine like terms: 6n + -6n = 0 10 + 2n = 12 + 0 10 + 2n = 12 Add '-10' to each side of the equation. 10 + -10 + 2n = 12 + -10 Combine like terms: 10 + -10 = 0 0 + 2n = 12 + -10 2n = 12 + -10 Combine like terms: 12 + -10 = 2 2n = 2 Divide each side by '2'. n = 1 Simplifying n = 1
| (x^2-10x-24)/(5x^3-20x) | | Y+5(1)=0 | | 30-r=-8 | | 16×10/3 | | p/12-9=-9 | | 4x+3+3=7x | | 14+11x+55=19x+5 | | 5.6/0.4 | | c+15=-50 | | 14+11x+55=19x*5 | | 10-3t=t+4 | | 6x-8x+6=x-4+10 | | -4b-32=5(1+7b)+2 | | 117/(-1)= | | 8+x+12=2x+20 | | 4x-6+5=13 | | -105=-8(-2-4p)+7 | | graph=-3x+2 | | -7+3x=-22 | | -2(x-5y)= | | graphy=-3x+2 | | 2x+4y-z=0 | | 3.5(m-6)=7m+19 | | n/8-7n/16= | | -21=-d+2 | | 0.68y+5=y-0.6 | | 2x+28+10=x+28 | | a+12=34 | | 1/2(6x-14)-1/3(21x-2y) | | 10x^5=-1250x^2 | | 3w-6+2w=-2(3a+8) | | (1)/(2)m-4=5 |